Investigation of PO43- Removal in Aerated and Unaerated High Fe EAF-Slag Filter System - R, Hamdan; Zu Nurain Ahmad, Siti; ‘Ain Nazirah Mohd Arshad, Nur; Afnizan Wan Mohamed, Wan; Nizam Maarup, Syahrul (International Journal of Engineering and Technology, 2018)
Phosphorus in wastewater is one the main culprit which accelerates eutrophication in waterbody if it is not being treated properly. Steel slag filter emerged as one alternative treatment for wastewater. However, the variousness of metal oxides including Fe in steel slag will affect the phosphorus removal efficiency. Thus, this study was conducted to investigate the ability of a series of lab-scale high Fe electric arc furnace (EAF- slag) column filters in removing PO43- from synthetic wastewater. The systems were operated under aerated and unaerated within acidic and alkaline conditions. Synthetic wastewater contained 25 mg/L was prepared as the feed and monitored weekly basis for the PO43- removal efficiency and the total metals (Ca, Fe, and Mg) concentrations in the effluents. The results show that both aerated and unaerated high Fe EAF-slag filter systems have high PO43- removal efficiency under acidic condition, which unaerated system performed slightly better. It can be observed that unaerated systems performed better in removing PO43- at acidic and neutral pH values but not at extremely high pH. As for the PO43- removal mechanism was achieved by adsorption and precipitation at acidic pH and the concentration of Ca, Mg and Fe in effluents was related to the PO43- removal efficiency at different pH values.Â Â